External validation of the Donor Risk Index and the Eurotransplant Donor Risk Index on the French liver transplantation registry. (23rd February 2017) - Winter, Audrey; Féray, Cyrille; Audureau, Etienne; Écochard, René; Jacquelinet, Christian; Roudot‐Thoraval, Françoise; Duvoux, Christophe; Daurès, Jean‐Pierre; Landais, Paul
Abstract: Background & Aims: A major limitation to liver transplantation is organ shortage leading to the use of non‐optimal liver grafts. The Donor Risk Index has been validated and recommended to select donors/organs. The Eurotransplant Donor Risk Index was derived from the Donor Risk Index. The objective of our study was to perform an external validation of both Donor Risk Index and Eurotransplant‐Donor Risk Index against the French liver transplantation Cristal registry according to recommendations of the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis. Methods: Liver transplantations performed in France between 2009 and 2013 were used to perform the validation study for the Donor Risk Index and the Eurotransplant‐Donor Risk Index respectively. We applied on the French data the models used to construct the Donor Risk Index and the Eurotransplant‐Donor Risk Index respectively. Results: Neither the Donor Risk Index nor the Eurotransplant‐Donor Risk Index were validated against this dataset. Discrimination and calibration of these scores were not preserved according to our data. Important donor and candidates differences between our dataset and the Organ Procurement and Transplantation Network or the Eurotransplant datasets may explain why the Donor Risk Index and the Eurotransplant‐Donor Risk Index appeared unadapted to the French transplant registry. Conclusion: Neither of these risk indexes were suitable to optimize the French liver allocation system. Thus, our next step will be to propose a general adaptive model for a Donor Risk Index.